AI-Augmented Game-Based Learning for Enhancing Arabic Speaking Skills: Evidence from a Quasi-Experimental Study - Mustaghfirin; Masrun; Rusdi (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2026)
This study investigates the effectiveness of AI-augmented game-based learning in enhancing Arabic speaking skills (maharah kalÄm) among junior secondary students. Employing a quasi-experimental design with a pretestâ€“posttest control group, the study was conducted at SMP Islam Baitul Qurâ€™an Riau involving 40 students divided into an experimental group and a control group. The experimental group received Arabic speaking instruction through a Truth or Dare game designed with instructional support from artificial intelligence, while the control group followed conventional instruction. Data were collected through speaking tests and analyzed using paired-samples and independent-samples t-tests. The findings reveal that both groups showed improvement; however, the experimental group demonstrated a significantly higher increase in speaking performance than the control group. These results indicate that integrating game-based learning with AI-supported instructional design can create a more interactive and communicative learning environment, thereby effectively improving Arabic speaking skills